Publisher Correction: Superplasticity in a lean Fe-Mn-Al steel - Jeongho Han (Nature Communications, 2018)
The original PDF version of this Article omitted to state that “Jeongho Han and Seok-Hyeon Kang contributed equally to this work” in the affiliations section. This has now been corrected in the PDF version of the Article. The HTML version was correct from the time of publication.